On Spectral Characterization of Nonuniform Hyperbolicity. (14th December 2017) - Abu Alhalawa, Muna; Dragičević, Davor
Abstract : We give a complete functional theoretic characterization of tempered exponential dichotomies in terms of the invertibility of certain linear operators acting on a suitable Frechét space. In sharp contrast to previous results, we consider noninvertible linear cocycles acting on infinite-dimensional spaces. The principal advantage of our results is that they avoid the use of Lyapunov norms.